ANALISIS BIAYA PRODUKSI BERDASARKAN JOB ORDER DAN PROCESS COST METHOD DALAM PENENTUAN HARGA JUAL - Hendriawan, Muhammad; Widiawati, Hestin Sri; Tohari, Amin (Universitas Nusantara PGRI Kediri, 2022)
This study aims to determine the analysis of production costs with the job order cost method and the analysis of production costs with the process cost method on determining the selling price of products in UD. Kerja Bersama Research.ini.using a descriptive approach and quantitative research. The data used are primary and secondary data. The data collection procedure is observation, documentation and direct interview to the object of study. The results of this study are that, within the UD. Kerja Bersama production costs and selling prices of products based on the job order cost method are higher than the process cost method. Because there is a difference in each element of costs incurred in the two methods so that it will affect the determination of the selling price of the product. The conclusion of this study shows that the process cost method has a lower cost value than the job order cost method, based on the difference in costs incurred by the job order is higher than the cost method.